Improving Active Resonance Damping and Unbalanced Voltage Mitigation Based on Combined DDSRF and Washout Filter in Islanded Microgrids - Ehsan Akbari (10803914) (2024)
The existence of imbalanced single- and two-phase loads, coupled with short-circuit faults, contributes to voltage imbalance. It is inevitable to use LCL filters to remove harmonics caused by converter switching. While effective in removing harmonic components, these filters may inadvertently amplify and propagate resonance. Both voltage imbalance and active resonance significantly degrade power quality. This paper proposes a multi-level hierarchical control system to mitigate both phenomena. At Level 1, the controller incorporates proportional-resonant regulators for current and voltage. Level 2 employs common droop control to establish microgrid voltage and frequency reference values. Level 3 introduces a washout filter with an adjustable Kd gain, capable of attenuating active resonance harmonics originating from the LCL filter. Finally, Level 4 integrates a controller based on extracting positive and negative sequence components using the dual decoupled synchronous reference frame (DDSRF) algorithm. This controller effectively compensates for negative sequence components of voltage in the load bus, balancing load voltage. Simulation results for a standalone microgrid demonstrate that the proposed 4-level hierarchical control algorithm can reduce the load bus voltage imbalance from 10% to 2.5% under the most challenging conditions. It diminishes harmonic distortion caused by active resonance from 11% to 2.5%. The presented control algorithm can perform optimally under dynamic changes of active and reactive power of nonlinear and imbalanced loads. The main merit of this approach is not to use physical devices and Flexible Alternative Current Transmission Systems (FACTS), such as Active Power Filters (APF), Distribution Static Synchronous Compensators (DsSTATCOM), SVC, etc. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2024.3393832